2019
DOI: 10.3390/met9050545
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rapid Heating and Fast Cooling on the Transformation Behavior and Mechanical Properties of an Advanced High Strength Steel (AHSS)

Abstract: The major goal of this work was to study the effect of rapid heating and fast cooling on the transformation behavior of 22MnB5 steel. The effect of the initial microstructure (ferrite + pearlite or fully spheroidized) on the transformation behavior of austenite (during intercritical and supercritical annealing) in terms of heating rates (2.5, 30 & 200 °C/s) and fast cooling, i.e., 300 °C/s rate, were studied. As expected, the kinetics of austenite nucleation and growth were strongly related to the heating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The results suggest that LA regions decompose to a mixture of ferrite and possible bainite, while prior HA regions are transformed mainly to martensite due to the inhomogeneous distribution of alloying elements in austenite. These results concur with those reported for lean alloy steels subjected to ultrafast heating and fast cooling [15,49,[53][54][55].…”
Section: Discussionsupporting
confidence: 92%
“…The results suggest that LA regions decompose to a mixture of ferrite and possible bainite, while prior HA regions are transformed mainly to martensite due to the inhomogeneous distribution of alloying elements in austenite. These results concur with those reported for lean alloy steels subjected to ultrafast heating and fast cooling [15,49,[53][54][55].…”
Section: Discussionsupporting
confidence: 92%
“…The surface of the workpiece may reach elevated temperatures, but if the heating and cooling down cycle is rapid enough, the induced thermal stress may be temporary and return to zero once the temperature again becomes homogeneous. On the other hand, heat-induced phase transformations take place only if the time spent at high temperatures is long enough, as they often depend on the heating and cooling rates [36,37]. Therefore, knowing the maximum temperature reached may not be enough to explain or predict the thermal damage.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that the final martensite volume fraction changed with an increase of the holding time in the austenite temperature range of 800-900 • C. Zhang et al [12] studied the phase transformation in the hot stamping process of USIBOR 1500 high-strength steel based on the Kirkaldy-Venugopalan model during the pressure holding quenching process. Pedraza et al [13] studied the effect of rapid heating and fast cooling on the transformation behaviour and mechanical properties of 22MnB5 steel. Mori et al [14] developed smart hot stamping of ultra-high strength steel products using rapid resistance heating and mechanical servo press.…”
Section: Introductionmentioning
confidence: 99%